Abnormalities of chromosome 17 in oesophageal cancer. Issue 9 (17th October 2006) - Moodley, Revendran; Reddi, Anunathan; Chetty, Runjan; Naidoo, Richard
Abstract : Background: Oesophageal cancer is the most common malignancy encountered in South African males, especially in the Eastern Cape and surrounding region of South Africa. There are a number of risk factors and predisposing conditions that have been implicated in the aetiology of the disease. The tylosis oesophageal cancer ( TOC ) gene, localised to a small region on chromosome 17q25, has been shown to be associated with oesophageal squamous cell carcinoma. Aim: To investigate loss of heterozygosity (LOH) and microsatellite instability (MSI) in the region of the TOC locus. Methods: In 74 oesophagectomy specimens for squamous cell carcinoma, microsatellite PCR was performed using five fluorescently labelled TOC markers. The PCR products were analysed and the data correlated with clinicopathological findings. Results: LOH ranged from 25% to 60%. LOH for the individual markers was as follows: D17S1839, 25%; D17S1864, 36%; D17S1817, 38%; D17S785, 47.8%; and D17S579, 60%. MSI ranged from 4.1% to 6.8% for the five loci in the 17q region. MSI was 4.1% for the markers D17S579, D17S785 and D17S1817. Marker D17S1864 showed MSI to occur in 4 cases (5.4%) and marker D17S1839 in 5 cases (6.8%). Conclusion: No significant relationship between genetic and clinical parameters was observed; however, aberrations in poorly differentiated tumours were high for markers D17S579 and D17S1864 (25% and 37%, respectively), indicating that these markers may have an underlying role in the molecular pathogenesis of oesophageal squamous cell carcinoma. In addition, 63% of patients who died showed LOH for the markers D17S579, D17S1864 and D17S1817.